LEGAL LANDSCAPE OF BLOCKCHAIN TECHNOLOGY AND LAND REGISTRATION IN INDONESIA - Evan Tjoa Putra; Lewiandy (Jurnal Hukum Lex Generalis, 2024)
Blockchain technology provides exceptional potential for the elimination of the inefficiencies and vulnerabilities in the land registry system in Indonesia. This paper therefore examines the incorporation of blockchain in land registration by use of a legal analysis, while studying the current framework and pointing out key challenges such as data privacy, reliabilities of smart contract enforcement, and liability in decentralized systems. It underlines the need for legal reforms in the amendment of existing land laws and harmonization with information technology regulations such as the ITE Law and the Law on the Operation of Electronic Systems. However, effective implementation enforces regulatory frameworks that respond to the various complexities introduced by blockchain technology in an efficient manner, at the same time offering legal certainty and protection to all the parties involved. Indonesia can modernize the part of its processes related to land registration by applying blockchain, which at some point could reduce fraud and increase public trust in the land records system.